Persistent photoconductivity in strontium titanate fibers, estimation of surface and deep traps (BISTUA Revista de la Facultad de Ciencias Básicas, 2023)
The growth of single-crystalline fibers of SrTiO3 using the LHPG technique is reported, in which persistent photoconductivity (PPC) was observed. The study was conducted for three cases of PPC induction. The average PPC time was determined for each case by estimating the carrier lifetimes in the recombination and trap states. The presence of surface and deep traps, along with their respective activation energies, was also estimated.
Keywords: Persistent photoconductivity; LHPG technique; Strontium titanate; Growth of single crystal fibers